2021
DOI: 10.38212/2224-6614.3387
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-induced antitumor effects on triple-negative breast cancer patient-derived xenograft tumor mice through inhibiting salt-induced kinase-3 protein

Abstract: This study demonstrated for the first time that curcumin effectively inhibits the growth of triple-negative breast cancer (TNBC) tumors by inhibiting the expression of salt-induced kinase-3 (SIK3) protein in patient-derived xenografted tumor mice (TNBC-PDX). For TNBC patients, chemotherapy is the only option for postoperative adjuvant treatment. In this study, we detected the SIK3 mRNA expression in paired-breast cancer tissues by qPCR analysis. The results revealed that SIK3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Cyclin D1 was analyzed to be an important ERα-dependent gene and cell cycle regulator (Fig. 3 B) [ 58 , 59 ]. A decrease in ERα expression and PARP cleavage in MCF7 cells were accompanied by a slight decrease in cyclin D1 expression at a concentration of 15 µM when fulvestrant treatment did not affect cyclin D1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin D1 was analyzed to be an important ERα-dependent gene and cell cycle regulator (Fig. 3 B) [ 58 , 59 ]. A decrease in ERα expression and PARP cleavage in MCF7 cells were accompanied by a slight decrease in cyclin D1 expression at a concentration of 15 µM when fulvestrant treatment did not affect cyclin D1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The research suggested curcumin as a potential anti-TNBC due to its ability to promote apoptosis, and to block the cell cycle of TNBC cells (MDA-MB-231) by inhibiting restoring DLC1 and EZH2 expression; it also inhibited the migration, invasion, and proliferation in vitro and in vivo studies with an IC 50 value at 40 µM for both MDA-MB-231 and MDA-MB-468 cell lines [191]. Other research showed that curcumin inhibited the SIK3-mediated cyclin D upregulation in the G1/S cell cycle and inhibited cell growth during epithelial-mesenchymal transition (EMT), with an IC 50 value of 25 µM in the MDA-MB-231 cell line by in vitro and in vivo studies [192].…”
Section: Curcuminmentioning
confidence: 98%
“…Curcumin mediates its promising activities by regulating several key molecular targets. They include (1) transcription factors [e.g., activator protein (AP)-1, β-catenin, NF-κB, peroxisome proliferator-activated receptor (PPAR)-γ, and signal transducer and activator of transcription (STAT)] [1, 2, 9, [19][20][21][22], (2) enzymes [e.g., cyclooxygenase (COX)2, 5-lipoxygenase (LOX), heme oxygenase-1 (HO-1), and inducible nitric oxide synthase (iNOS)] [1,2,9,19,20,23,24], (3) protein kinases [mitogen-activated protein kinases (MAPKs), Janus kinase (JAK), adenosine monophosphateactivated protein kinase (AMPK), protein kinase A (PKA), and PKC [2, 9, 19-22, 24, 25], (4) cell cycle proteins (e.g., cyclin D1 and E) [1,2,9,[19][20][21]25], (5) cytokines [e.g., tumor necrosis factor (TNF), interleukins (ILs)-1 and 6, and chemokines] [1,2,20], (6) receptors [e.g., epidermal growth factor receptor (EGFR) and human EGFR (HER)2)] [2,9,19,20,23], (7) cell surface adhesion molecules [e.g., intercellular adhesion molecule (ICAM)-1, vascular cell adhesion molecule (VCAM)-1, and endothelial leukocyte adhesion molecule (ELAM)-1 [2,20], and (8) genes that regulate cell proliferation and apoptosis (e.g., p21, p27, and p53) [1,2,9,[19]…”
Section: Molecular Mechanism and Pharmacology Of Curcuminmentioning
confidence: 99%